Fourier transform infrared studies of the N₂–O₂ binary system - Minenko, M.; Jodl, H.-J. (Физика низких температур, 2006)
Solid solutions (N₂)x(O₂)₁₋x have been investigated by infrared absorption measurements mainly in the O₂ and N₂ stretching regions, between 60–10 K, completing former similar studies by Raman scattering. We produced thermodynamically stable samples by a careful thermal treatment, followed by cooling/heating cycles over weeks, during which we took spectra. From fingerprints in infrared spectra we deduce phase transition lines, solubility lines and suggest a refined, improved T–x% phase diagram with respect to inconsistencies between those in literature. Spectra of N₂–O₂ mixtures are pretty complex but referring to known spectra of pure systems N₂ or O₂ we were able to assign and interpret broad (~100 cm⁻¹) phonon side bands to fundamentals and electronic transition (O₂) depending on actual temperature and concentration. Narrow features in spectra (<10 cm⁻¹) were attributed to the vibron DOS of N₂ or O₂, whose bandwidth, band shape and intensity are different and characteristic for each phase. Differences between pure and mixed systems were pointed out. Matrix isolation technique (2 ppm of CO) was used to probe our mixture.